Quality evaluation of guava (Psidium guajava L. ) chewable toothpaste tablets: a preliminary study/ Zaidatul Shakila Mohamad Ashari and Nunshaimah Salleh - Mohamad Ashari, Zaidatul Shakila; Salleh, Nunshaimah (2023)
This project's goal is to assess the quality of guava (Psidium guajava L.) chewable toothpaste tablets. Toothpaste tablets with charcoal, without charcoal, without humectant, and with charcoal using liquid stevia were the four different formulations created. In this study, the functional groups found in guava powder and formulated guava chewable toothpaste tablets were compared using FTIR, and the cleaning ability efficacy of guava chewable toothpaste tablets using eggshells were determined.